PENGARUH KONSENTRASI KEPEMILIKAN, KOMISARIS INDEPENDEN, DAN KUALITAS AUDIT TERHADAP EARNING PER SHARE (EPS) - Dabella Yunia (Jurnal Riset Akuntansi Terpadu, 2018)
The objective of this research is examine the concentration of ownership, independent commissioners, and audit quality to earning pe share (EPS). The study population is all companies listed on the Indonesia Stock Exchange. The sample of this research is a manufacturing company listed on Indonesia Stock Exchange 2012-2013. Tests of this research using multiple regression method. The results of this study prove that the variable of ownership concentration and audit quality influence to earnings per share (EPS), while independent commissioner variables have no effect on earnings per share (EPS).